Sob a insígnia da raça: a concepção de nação e a representação do negro n’O Mulato de Aluísio Azevedo (1881) - MAURÍCIO, Marlzonni Marrelli Matos (2017)
This dissertation presents research on the Negro in the novel O mulato, as well as in the concept of nation by Aluísio Azevedo, in 1881. In this way, the Negro is apprehended as an individual and an imagined being, represented, both in the formation of the literary canon and in the national formation. Considering also their presence in the racial theories, in slavery and abolitionist discourses. For the thematic contribution, the research is based on an extensive bibliography, comprising works by historians and sociologists to literary critics and philosophers. For the theoretical contribution, the theory developed by Roger Chartier, Pierre Bourdieu, Sandra Jathay Pesavento, among other intellectuals, is used. The sources consist of written texts, which are basically novels and newspapers of the time. This dissertation, therefore, intends to investigate whether O mulato is an anti-racist novel, or if this is only a mere sophistry.